2016
DOI: 10.1364/ao.55.005721
|View full text |Cite
|
Sign up to set email alerts
|

Phase error analysis and compensation for phase shifting profilometry with projector defocusing

Abstract: Phase shifting profilometry (PSP) using binary fringe patterns with projector defocusing is promising for high-speed 3D shape measurement. To obtain a high-quality phase, the projector usually requires a high defocusing level, which leads to a drastic fall in fringe contrast. Due to its convenience and high speed, PSP using squared binary patterns with small phase shifting algorithms and slight defocusing is highly desirable. In this paper, the phase accuracies of the classical phase shifting algorithms are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…, and k 0 are also the fitting coefficients after transformation calculation in formula (20). It is concluded that there is actually a nonlinear response of order 3c in the measurement system.…”
Section: Phase Error Compensation Methods Based On Phasementioning
confidence: 99%
See 1 more Smart Citation
“…, and k 0 are also the fitting coefficients after transformation calculation in formula (20). It is concluded that there is actually a nonlinear response of order 3c in the measurement system.…”
Section: Phase Error Compensation Methods Based On Phasementioning
confidence: 99%
“…ree-Frequency with ree-Phase Shifts. e multifrequency heterodyne method usually projects sinusoidal fringe pattern sequence with multifrequency to measure the object, and then, a set of phase distribution with smaller frequency will be obtained from their heterodyne calculation [19,20]. erefore, it is necessary to select both the sinusoidal fringe with appropriate frequency and the appropriate period T 1 , T 2 , and T 3 .…”
Section: Reverse Calculation Initial Phase Methods Based Onmentioning
confidence: 99%
“…In FPP systems that employ structured-light projectors, nonsinusoidal error can dominate as the major error. Nonsinusoidal phase errors can be satisfactorily modeled as a periodic sinusoidal function with multiple spatial frequencies of a multiple number of phase-shifting steps [31,32,33,34,35]:σϕ2=i=0N1][ϕIi2σ2…”
Section: Literature Reviewmentioning
confidence: 99%
“…The similar model based on the Hilbert transform was also proposed to eliminate the phase error [ 28 ]. Zheng et al applied the above two methods to the phase error correction of BGPSP with projector defocusing [ 29 ]. In addition, a large-step phase-shifting method can be used to eliminate the non-linearity error [ 30 ].…”
Section: Introductionmentioning
confidence: 99%